Anomalies of the cerebral arteries in military servants - participants of ATO-OOS, who suffered ischemic strokes - Viktor Teshchuk; Nazarii Teshchuk; Oleksandr Ruskykh (Kazimierz Wielki University, 2021)
The analysis of medical histories of 129 patients aged 20 to 59 years, who suffered acute cerebrovascular disorders (AСVD) of the ischemic type (IT), and participated in ATO-JFO was carried out. Anomalies of cerebral arteries were found in all of them. A significant role of hypoplasia of the right posterior cerebral artery, aplasia of the posterior connective, left anterior cerebral and anterior connective, as well as pathological S-shaped tortuosity of the internal carotid artery, hypoplasia of the vertebral arteries and their combinations in the development of acute cerebrovascular disorders in ATO members was established.